Clinical Outcomes of Laparoscopic Versus Open Appendectomy for Acute Appendicitis in a Resource-limited Setting - Mohanned Omer Abass (The Annals of African Surgery, 2021)
Background: Acute appendicitis is the most common cause of the acute abdomen; thus, appendectomy is part of most daily emergency surgical duties. It is conducted through either open or laparoscopic approach. Methods: A prospective hospital-based study compared the clinical outcomes of open versus laparoscopic appendectomy for patients with acute appendicitis in El-Mek Nimir University Hospital, Sudan. Results: A total of 550 cases of acute appendicitis were studied, of which 328 (59.6%) underwent open appendectomy surgery and 222 (39.4%) underwent laparoscopic appendectomy. The majority of the study’s population was female. Laparoscopic appendectomy generally involved a longer operation time than open appendectomy (mean duration, 42.4±12.5 vs. 29±16 minutes), lesser incidence of severe pain postoperatively (3% vs. 11%; p=0.000), shorter hospital stay (i.e., <24 hours; 96% vs.77%; p=0.000), and a higher rate of patient return to normal activities within 1 week (92% vs.15%; p=0.000). Differences in the occurrence of bleeding, wound infection, or intra-abdominal septic collection were not statistically significant. Conclusion: Both open and laparoscopic appendectomy procedures are safe for the management of acute appendicitis; however, laparoscopic appendectomy is associated with fewer complications and a faster recovery.